Factors affecting the performance of airline ticket sales of Malaysia Airlines System Berhad / Anis Amira Mukhtar@Muhammad - Mukhtar@Muhammad, Anis Amira (Faculty of Business and Management, 2011)
The purpose of this case study is to identify the factors that affect sales performance of an organization, which in this context, the performance of airline ticket sales of Malaysia Airlines. After going through supporting journals on the factors, the researcher then will analyze if Malaysia Airlines do practice the theory found in the supporting journals. Here, the researcher would examine if there is any gap between the one in the theory and the one practiced by the company. Having that done, the researcher will analyze if the factors practiced by the company have significant effect on the performance of airline ticket sales. Then the researcher will move on to the recommendation as to improve the performance of airline ticket sales of Malaysia Airlines.